Battery electric vehicle adoption in Portugal and the Netherlands - Samsom, Boudewijn (2021)
Even though the need for an emission reduction is clearer than ever, the electrification of the transport industry is not as rapid as it could be. What is holding back the mass adoption of BEVs? An important reason is that the adoption of BEVs is largely dependent on the acceptance of private consumers, and their willingness to adopt this mode of transport is insufficient. The main barriers of limiting range, high purchase price and insufficient charging network are important to tackle in order to achieve mass adoption of electric vehicles. In this paper, policy and incentive awareness, technological characteristic awareness, environmental awareness, tech savviness, mobility characteristics and demographics are tested to better understand the main reasons for adoption. A cross-country analysis is done between the Netherlands and Portugal to see if these reasons might differ per country. An online survey is conducted to answer the main questions. 400 responses are gathered and analyzed to understand what variables are important to achieve mass adoption.